2013
DOI: 10.3928/21650799-20130418-66
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Cigarette Smoking and Occupational Exposures on Lung Function: A Cross-sectional Study of Rubber Industry Workers

Abstract: Workers in the rubber industry are exposed to pulmonary health hazards. The main purpose of this study was to assess the combined effect of cigarette smoking and occupational exposures on lung function. The exposed group consisted of tire manufacturing workers in production units and the non-exposed group included executives from the same factory. The researchers calculated the synergy index (SI) to determine the combined effect of exposures to cigarette smoke and pulmonary health hazards on lung function. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In line with our results, Maritta et al, demonstrated that smoking has a synergistic effect to dust on lung function of tile factory workers (12). In this regard, Attarchi et al reported a signi cant synergistic effect of cigarette smoking and occupational exposures on lung function of rubbery workers (13). These ndings revealed that cigarette smoking has been implicated as a risk factor for respiratory disease among industry workers.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, Maritta et al, demonstrated that smoking has a synergistic effect to dust on lung function of tile factory workers (12). In this regard, Attarchi et al reported a signi cant synergistic effect of cigarette smoking and occupational exposures on lung function of rubbery workers (13). These ndings revealed that cigarette smoking has been implicated as a risk factor for respiratory disease among industry workers.…”
Section: Discussionsupporting
confidence: 92%
“…Table summarizes 32 articles describing 30 cross‐sectional studies evaluating the presence of respiratory symptoms and NMRD among workers exposed to rubber manufacturing emisssions . Occupational cohorts ( n = 10 896 workers in total) across studies varied from 34 to 1820 workers, and included facilities from the United States ( n = 14), Sweden (6), India (3), Iran (3), Italy (1), Netherlands (1), Poland (1), and Turkey (1).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐six (87%) of the cross‐sectional studies assessed for tobacco use among workers; 19 (63%) of those studies reported respiratory symptoms or lung function associated with smoking. For example, one study described prevalence of lung impairment among exposed non‐smokers (odds ratio = 3.45, 95%CI, 1.76‐9.50), exposed smokers (12.12, 3.35‐37.87), and non‐exposed smokers (3.48, 1.42‐8.33) compared with non‐exposed non‐smokers …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the encountered general manifestations of loss of appetite, loss of weight, persistent weakness or fatigability, and bony aches showed a highly statistically significant prevalence among exposed workers when compared with their controls. These general toxic manifestations were attributed to the hazardous exposure to various toxic chemicals involved in the rubber industry such as aromatic amines, carbon black, nitrosamines, phthalates, polycyclic aromatic hydrocarbons, and solvents, in many different processes (Attarchi et al, 2013;Wingren and Axelson, 2007). In the rubber manufacturing industry, light naphtha made of aliphatic hydrocarbon (n-hexane) and aromatic hydrocarbons (benzene, ethyl benzene, toluene, xylene, and cumene) could be used as solvents in the production processes.…”
Section: Hscrpmentioning
confidence: 99%